2005
DOI: 10.1248/bpb.28.1873
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect of Chotosan, a Kampo Medicine, on Transient Ischemia-Induced Learning Deficit Is Mediated by Stimulation of Muscarinic M1 But Not Nicotinic Receptor

Abstract: We have previously shown using a water maze task that transient 2 vessel occlusion (T2VO) induced learning deficit in mice and that the deficit was prevented by pre-treatment of mice with chotosan, a Kampo prescription. In this study, we investigated the mechanism underlying the preventive effect of chotosan on T2VO-induced learning deficit. Chotosan administration 1 h before T2VO operation prevented learning impairment. The extract of Uncaria, a major constituent of chotosan, also had a protective effect on l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 30 publications
(55 reference statements)
2
23
0
Order By: Relevance
“…In our study using a mouse model of transient cerebral ischemia (T2VO), single administration of CTS extract, at doses (375 -750 mg/kg per day, p.o.) equivalent to about 10 to 30 times the daily dose used for human therapy, exhibited a preventive effect on T2VO-induced spatial cognitive deficits in a manner reversible by a muscarinic M 1 -receptor antagonist, pirenzepine, but not by a nicotinic receptor antagonist, mecamylamine (18). Moreover, in a mouse model of permanent occlusion of common carotid arteries (P2VO), we found that daily administration of CTS (750 mg/kg per day, p.o.)…”
Section: Neuropharmacological Aspects Of Cts and Yks As Putative Antimentioning
confidence: 78%
“…In our study using a mouse model of transient cerebral ischemia (T2VO), single administration of CTS extract, at doses (375 -750 mg/kg per day, p.o.) equivalent to about 10 to 30 times the daily dose used for human therapy, exhibited a preventive effect on T2VO-induced spatial cognitive deficits in a manner reversible by a muscarinic M 1 -receptor antagonist, pirenzepine, but not by a nicotinic receptor antagonist, mecamylamine (18). Moreover, in a mouse model of permanent occlusion of common carotid arteries (P2VO), we found that daily administration of CTS (750 mg/kg per day, p.o.)…”
Section: Neuropharmacological Aspects Of Cts and Yks As Putative Antimentioning
confidence: 78%
“…This observation is supported by the findings reported by Sharma et al (23) that adult (10 -11-week-old) db/db mice are hypolocomotive as evident by a decrease of basic and fine movements. On the basis of this fact, we adopted a 120-s observation period instead of a conventional 60-s observation period (6,20) for O-db/db mice and age-matched control m/m mice, in the training and probe tests of the water maze task in order to reduce contribution of different swimming abilities to their cognitive performance. This protocol clearly indicated that vehicle-treated O-db/db mice exhibit spatial cognitive deficits compared with agematched m/m control strain mice.…”
Section: Discussionmentioning
confidence: 99%
“…The water maze test was performed by slightly modifying the protocol adopted in previous studies (6,20). Briefly, the water maze testing took place during the first half of the light phase.…”
Section: Water Maze Testmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13) Moreover, pharmacological studies have suggested that the anti-dementia effects of CTS are due to its anti-hypertensive, 14,15) free radical scavenging, 16) anti-excitotoxic effects, [17][18][19][20] improvement of microcirculation, 14) protection of endothelial function, and enhancement of central cholinergic systems. [21][22][23] Recently, Tohda et al 24) have reported using DNA microarray analysis and RT-PCR that permanent occlusion of bilateral common carotid arteries (P2VO) of rats, an animal model of cerebral hypoperfusion, [25][26][27][28] significantly elevated the expression level of M-CSF mRNA in the cerebral cortex of rats. This finding led us to hypothesize that M-CSF in the brain may be involved in the beneficial effects of chotosan in the treatment of patients with vascular dementia.…”
mentioning
confidence: 99%